Clinical implications of scapular dyskinesis in shoulder injury: the 2013 consensus statement from the `scapular summit` - Kibler, W. B.; Ludewig, P. M.; McClure, P. W. (British Journal of Sports Medicine, 2013)
The second international consensus conference on the scapula was held in Lexington Kentucky. The purpose of the conference was to update, present and discuss the accumulated knowledge regarding scapular involvement in various shoulder injuries and highlight the clinical implications for the evaluation and treatment of shoulder injuries. The areas covered included the scapula and shoulder injury, the scapula and sports participation, clinical evaluation and interventions and known outcomes. Major conclusions were (1) scapular dyskinesis is present in a high percentage of most shoulder injuries; (2) the exact role of the dyskinesis in creating or exacerbating shoulder dysfunction is not clearly defined; (3) shoulder impingement symptoms are particularly affected by scapular dyskinesis; (4) scapular dyskinesis is most aptly viewed as a potential impairment to shoulder function; (5) treatment strategies for shoulder injury can be more effectively implemented by evaluation of the dyskinesis; (6) a reliable observational clinical evaluation method for dyskinesis is available and (7) rehabilitation programmes to restore scapular position and motion can be effective within a more comprehensive shoulder rehabilitation programme.